PENGARUH PENDIDIKAN DAN PELATIHAN (DIKLAT) TERHADAP KINERJA KARYAWAN CV MAHATAMA KARYA - Arif Rahman; Jaenudin Akhmad; Yosi Suranti (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to determine the effectiveness of education and training(diklat), to determine the obstacles that occur, and to determine the solutions taken toovercome obstacles to employee performance at CV Mahatama Karya. The research method used in this study is quantitative research with a correlational approach at CV Mahatama Karya. Every company often faces problems with employee performance, therefore, education and trining become a means of coaching and career development. CV Mahatama Karya has also provided various training to its employees, but the training provided has not been optimal and the number of employees who have participated in the training is still too small so that the performance produced has not been optimal.